2009
DOI: 10.1021/es9017464
|View full text |Cite
|
Sign up to set email alerts
|

Electrode-Based Approach for Monitoring In Situ Microbial Activity During Subsurface Bioremediation

Abstract: Current production by microorganisms colonizing subsurface electrodes and its relationship to substrate availability and microbial activity was evaluated in an aquifer undergoing bioremediation. Borehole graphite anodes were installed downgradient from a region of acetate injection designed to stimulate bioreduction of U(VI); cathodes consisted of graphite electrodes embedded at the ground surface. Significant increases in current density (≤50 mA/m 2 ) tracked delivery of acetate to the electrodes, dropping ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 41 publications
3
67
0
Order By: Relevance
“…However, taking also the use of plants and possible agricultural practices into account, this study has shown that granular materials can provide a good alternative. MFC-technology has been proposed as a means of alternative or enhanced soil or sediment remediation (Yuan et al 2010;Zhang et al 2010;Williams et al 2010). The idea behind this concept is to provide an extra electron donor or acceptor in the form of an electrode.…”
Section: Microbial Community and Materials Structurementioning
confidence: 99%
“…However, taking also the use of plants and possible agricultural practices into account, this study has shown that granular materials can provide a good alternative. MFC-technology has been proposed as a means of alternative or enhanced soil or sediment remediation (Yuan et al 2010;Zhang et al 2010;Williams et al 2010). The idea behind this concept is to provide an extra electron donor or acceptor in the form of an electrode.…”
Section: Microbial Community and Materials Structurementioning
confidence: 99%
“…In the field, the electrode spacing seems not so crucial. Results from a sensing probe (graphite anode embedded within a sand pack) for monitoring in situ microbial activity in an aquifer undergoing bioremediation, shows that MFC can produce detectable currents despite long range separation (6 m) between anode and cathode [148]. To overcome spacing issue, several setups are proposed as: tubular setup where the electrodes are separated only by a low-cost cloth and so the cathode catalytic surface (conductive paint + catalyst) inside the tube is directly exposed to air to allow efficient oxygen reduction; or 3D setup with multilayer or honeycomb anode structure.…”
Section: Surface Functionalisationmentioning
confidence: 99%
“…An oxygen reduction reaction is not a solution as this will be counterproductive towards mitigation of the eutrophication. However a long distance cathode (Williams et al, 2010) can be used when it is placed on the water surface where there is a lot of photosynthetic oxygen production. Another possibility is to make use of a nitrate reducing biocathode reaction .…”
Section: Outlook and Opportunitiesmentioning
confidence: 99%